2020
DOI: 10.1177/0954406220902168
|View full text |Cite
|
Sign up to set email alerts
|

The tribological properties of bearing alloys under oil lubrication

Abstract: In this article, the tribological behaviors of CuPb24Sn under different load and oil lubrication conditions were studied. The worn surface, material transfer, and debris of the material were analyzed by the scanning electron microscopy and energy-dispersive X-ray spectrometer. In addition, the wear rate of CuPb24Sn was measured by means of a laser microscopic 3D and profile measurement apparatus. The results show that the soft phase lead wears preferentially from the sample surface under both light and heavy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Li et al. 8 investigated the tribological and wear performance of CuPb24Sn considering different applied loads and oil lubrication conditions. It can be found that the wear mechanisms of CuPb24Sn under heavy-load conditions are composed of adhesive wear and oxidation wear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. 8 investigated the tribological and wear performance of CuPb24Sn considering different applied loads and oil lubrication conditions. It can be found that the wear mechanisms of CuPb24Sn under heavy-load conditions are composed of adhesive wear and oxidation wear.…”
Section: Introductionmentioning
confidence: 99%
“…In similar research, Tunay et al 7 conducted the tribological tests of 90Cu10Sn and 90Cu9Sn1C porous bearings with different oil temperatures, the results showed that as the oil temperature increases, the corresponding weight loss and friction coefficient increase. Li et al 8 investigated the tribological and wear performance of CuPb24Sn considering different applied loads and oil lubrication conditions. It can be found that the wear mechanisms of CuPb24Sn under heavyload conditions are composed of adhesive wear and oxidation wear.…”
Section: Introductionmentioning
confidence: 99%